First mercury and stable isotope assessment from an unusual mass stranding of rough-toothed dolphins (Steno bredanensis) (Artiodactyla: Delphinidae) in Azuero peninsula, Pacific coast of Panama - Barragán-Barrera, Dalia-C. (2023)
Introduction: Small cetaceans are good bioindicators of environmental contamination; however, knowledge about their ecotoxicological status in Central America is scarce. In Panama, access to samples from wild populations to determine the ecotoxicological status of oceanic dolphins is limited; therefore, stranding events provide an alternative for obtaining samples. In April 2016, a rare mass stranding event occurred in the Azuero Peninsula (Pacific coast of Panama), where 60 rough-toothed dolphins (Steno bredanensis) stranded, including ten which died on the beach. Objective: To assess total mercury (THg) concentrations, and δ13C and δ15N stable isotope values in rough-toothed dolphins for the first time in this region. Methods: Nine skin samples were collected from adults, stored in 70 % ethanol, and posteriorly analyzed to determine THg concentrations and stable isotope values. Results: THg concentrations ranged from 4 764 to 18 689 ng g-1 dry weight (dw) (mean = 12 841; SD = 5 083 ng g-1 dw), δ13C values ranged between −16.8 and −15.2 ‰ (mean = −16.2; SD = 0.6 ‰), and δ15N values ranged between 14.3 and 15.9 ‰ (mean = 15.0; SD = 0.5 ‰). Conclusions: High THg concentrations reported for this species in the Azuero Peninsula are consistent with values reported for rough-toothed dolphins in other areas worldwide, such as the central-northern Rio de Janeiro State in Brazil and La Guajira in the Colombian Caribbean. Elevated mercury (Hg) concentrations may be related to the rough-toothed dolphin diet, which according to δ15N values found here, appears to be based mainly on high trophic level prey that bioaccumulate more Hg in their tissues compared to lower trophic level organisms. However, additional dietary studies would be required to support these findings. Continuing monitoring of traditional dietary analysis, as well as contamination levels in fish and dolphins, is necessary to understand the dolphins’ ecotoxicology in Panama.